Post-pandemic: Teaching with kindness. (3rd July 2022) - Govender, Lynelle
Abstract: People like to use the word 'unprecedented' when they talk about 2020. An unprecedented virus, an unprecedented global impact, and an unprecedented way to teach. After two years of this rhetoric, the word can start to feel a little tired. Undoubtedly, in the face of COVID-19 we had to do things very differently, but this statement seeks to look beyond the pragmatic. This personal view examines how the past two years of experience have influenced my beliefs and behaviours as they relate to teaching. I reflect on the changing role I experienced as a teacher, and how I have come to understand the need for compassion and kindness.